Distribution of Streptococcus troglodytae and Streptococcus dentirousetti in chimpanzee oral cavities. (14th May 2013) - Miyanohara, Mayu; Imai, Susumu; Okamoto, Masaaki; Saito, Wataru; Nomura, Yoshiaki; Momoi, Yasuko; Tomonaga, Masaki; Hanada, Nobuhiro
Abstract The aim of this study was to analyze the distribution and phenotypic properties of the indigenous streptococci in chimpanzee (Pan troglodytes) oral cavities. Eleven chimpanzees (aged from 9 to 44 years, mean ± SD, 26.9 ± 12.6 years) in the Primate Research Institute of Kyoto University were enrolled in this research and brushing bacterial samples collected from them. Streptococci were isolated from the oral cavities of all chimpanzees. The isolates (n = 46) were identified as thirteen species by 16S rRNA genes analysis. The predominant species was Streptococcus sanguinis of mitis streptococci from five chimpanzees (45%). Mutans streptococci were isolated from six chimpanzees (55%). The predominant species in the mutans streptococci were Streptococcus troglodytae from four chimpanzees (36%), this species having been proposed as a novel species by us, and Streptococcus dentirousetti from three chimpanzees (27%). Streptococcus mutans was isolated from one chimpanzee (9%). However, Streptococcus sobrinus, Streptococcus macacae and Streptococcus downei, which are indigenous to human and monkey (Macaca fasciclaris) oral habitats, were not isolated. Of the mutans streptococci, S. troglodytae, S. dentirousetti, and S. mutans possessed strong adherence activity to glass surface.